Microwave Enhanced Synthesis of Flax-g-poly(MMA) for Use in Phenolic Composites as Reinforcement - Susheel Kalia; B. S. Kaith (E-Journal of Chemistry)
Graft copolymerization of methyl methacrylate (MMA) onto flax fiber under the influence of microwave radiations (MWR) was carried out. 24.64% grafting was found at 210W microwave power under optimum reaction conditions. The graft copolymers were characterized with FTIR spectroscopy, scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques. Graft copolymers thus prepared were used in the preparation of phenol-formaldehyde (PF) composites. Modulus of rupture (MOR), modulus of elasticity (MOE) and stress at the limit of proportionality (SP) of composites were measured and it has been found that composites reinforced with Flax-g-poly(MMA) showed better mechanical properties in comparison to composites reinforced with raw flax.